2005
DOI: 10.1002/ajmg.a.30774
|View full text |Cite
|
Sign up to set email alerts
|

Distinct phenotype associated with a cryptic subtelomeric deletion of 19p13.3‐pter

Abstract: Telomeres are gene rich regions with a high recombination rate. Cryptic subtelomeric rearrangements are estimated to account for 5% of mental retardation/malformation syndromes. Here we present the first patient with a deletion of 19p13.3, identified by subtelomeric FISH analysis. His features included a distinctive facial appearance, cleft palate, hearing impairment, congenital heart malformation, keloid scarring, immune dysregulation, and mild learning difficulties. Subtelomeric FISH analysis identified a de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
37
1
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(47 citation statements)
references
References 46 publications
8
37
1
1
Order By: Relevance
“…By standard cytogenetic G-band karyotyping, Hurgoiu and Suciu [1984] detected a deletion at 19p. Archer et al [2005] reported a deletion at 19p13.3-pter, detected by subtelomeric FISH analysis. Array CGH has uncovered 6 aberrations at 19p13; Engels et al [2007] described a deletion at 19p13.12, Thienpont et al [2008] a duplication and triplication at 19p13.11, Jensen et al [2009] a deletion at 19p13.12, Aten et al [2009 and psychomotor developmental delay; however, the symptoms of Patient 2 are less severe than those of Patient 1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…By standard cytogenetic G-band karyotyping, Hurgoiu and Suciu [1984] detected a deletion at 19p. Archer et al [2005] reported a deletion at 19p13.3-pter, detected by subtelomeric FISH analysis. Array CGH has uncovered 6 aberrations at 19p13; Engels et al [2007] described a deletion at 19p13.12, Thienpont et al [2008] a duplication and triplication at 19p13.11, Jensen et al [2009] a deletion at 19p13.12, Aten et al [2009 and psychomotor developmental delay; however, the symptoms of Patient 2 are less severe than those of Patient 1.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, we found only 8 published reports on isolated aberrations in the short arm of chromosome 19 [Hurgoiu and Suciu, 1984;Archer et al, 2005;Engels et al, 2007;Thienpont et al, 2008;Aten et al, 2009;Auvin et al, 2009;Jensen et al, 2009;Lysy et al, 2009]. In the earliest reports, aberrations were detected by karyotyping and in more recent reports by various fluorescent in situ hybridization (FISH) methods and array comparative genomic hybridization (array CGH).…”
mentioning
confidence: 99%
“…The most striking example of this was the elucidation of the '1p36 deletion syndrome' (Shapira et al, 1997;Knight-Jones et al, 2000). This was followed by clinically identifiable phenotypes being put forward for a number of other subtelomeric imbalances, for example, 1qter syndrome, 2q37.3 monosomy, 3q29 microdeletion syndrome, 5q35.3 subtelomeric deletion syndrome, 6q subtelomeric deletion syndrome, subtelomeric 9q microdeletion syndrome, 14q terminal deletion syndrome, 19p13.3-pter subtelomeric deletion syndrome and 22q deletion syndrome (de Vries et al, 2001a;van Karnebeek et al, 2002;Heilstedt et al, 2003;Rauch et al, 2003;Wilson et al, 2003;Aldred et al, 2004;Stevenson et al, 2004;Stewart et al, 2004;Archer et al, 2005;Eash et al, 2005; van Bever et Willatt et al, 2005). In most cases these studies were aided by the detailed phenotypic characterisation of a series of patients with similar regions of imbalance.…”
Section: Identifying Clinical Phenotypes Associated With Subtelomericmentioning
confidence: 98%
“…A deletion of about 1.2 Mb on chromosome 19p13.3 was identified in a patient with cleft palate, hearing impairment, congenital heart malformation, keloid scarring, immune dysregulation, and mild learning difficulties. The deleted area encompasses about 60 genes including FSTL3 (Archer et al, 2005).…”
Section: Somaticmentioning
confidence: 99%